Person centered care for primary ovarian insufficiency: developing and testing patient-facing materials co-created with patients - Blocker, Elizabeth S.; McDonald, Isabella R.; Weyman, Elizabeth A.; Jarvis, Dana L.; Bryce, Joni; Welt, Corrine K.; Dwyer, Andrew A. (Frontiers in Communication, 2025)
ObjectiveWe aimed to enhance person-centered care for primary ovarian insufficiency (POI) by co-creating patient-facing educational materials (PEM) with patients. We then evaluated understandability, actionability, and acceptability of the co-created PEM.DesignHealthcare professionals spanning reproductive endocrinology, nursing, and genetic counseling partnered with patients to co-create PEM using the iterative ‘design thinking’ (human-centered design) process. Validated algorithms (n = 8) were employed to determine PEM readability prior to evaluation. Individuals with POI were recruited from patient organizations to complete the online evaluation of PEM. Participants completed health literacy/numeracy instruments, Patient Education Materials Assessment Tool for print materials (PEMAT-P), and provided open-ended qualitative feedback. Scores >80% in PEMAT-P domains were considered ‘high quality’.ResultsCo-creation involved three iterative rounds of development. Readability algorithms indicated PEM were ‘fairly easy to read’ for 11- to 13-year-olds (i.e., 7th grade reading level). Thirty patients completed the online evaluation (36.9 ± 6.4 years-old). All PEMAT-P domains exceeded the ‘high quality’ threshold: content (82%), word choice/style (89%), use of numbers (91%), organization (93%), layout/design (90%), use of visual aids (83%), and actionability (85%). PEMAT-P scores neither differed according to educational attainment (p = 0.94) nor health literacy/numeracy (p = 0.61). Qualitative feedback informed further PEM refinement prior to widespread dissemination and clinical use.ConclusionEngaging patients with POI in co-creation produced PEM that were acceptable, understandable, and actionable. Co-creation is a low-cost engagement process supporting person-centered care. The process described herein may serve as a “roadmap” guiding PEM development for other reproductive conditions.